Doing the Right Thing Right: The Role of Sociological Research and Consulting for Corporate Engagement in Development Cooperation - Daub, Claus-Heinrich (Journal of business ethics, 2009)
The purpose of this article is to illustrate the role of sociology in the field of corporate social responsibility (CSR). It presents a case study conducted by a research group consisting of two University partners in association with a Swiss SME. This project attempted to draw conclusions from a specific sociological consultancy research project on the general possibilities and opportunities of sociology in applied research and operational sustainability consulting. On the basis of the project findings, the article reflects on the extent to which sociology could profitably intervene, on the limitations for sociological research and consultations in this field and on the conclusions that can be drawn for future analyses.